The interplay between short‐term, mild physicochemical forcing and plankton dynamics in a coastal area. (3rd May 2013) - Romero, Estela; Peters, Francesc; Guadayol, Òscar
Abstract : Two intensive surveys were conducted in the coastal waters of Barcelona (northwest Mediterranean) to assess short‐term variations of biological parameters in relation to environmental conditions. Surveys lasted 1 week, with three to four samplings per day, and were carried out in autumn and spring. Rather than exploring extreme events, we aimed to study the effects of regular low or moderate perturbations, such as meteorological fronts, on the dynamics of the system. We focused on two attributes: wave height, as a proxy for mechanical energy entering the system, and nutrient inputs, whose variability in total load and relative composition is a central characteristic of coastal areas. The effects of the temporal coupling or uncoupling of both factors were examined. Sudden nutrient fluxes uncoupled from water motion tended to favor bacteria and heterotrophic nanoflagellates, while their concurrence with some water column mixing shaped a favorable scenario for large autotrophs. Ultimately, these two distinct biological responses pointed toward two main disturbance scenarios: episodes of nutrient enrichment uncoupled from mixing, mostly related to episodic water spills from the nearby city that contributed to high relative loads of ammonium and organic compounds; and episodes of increased wind caused by passing weather fronts that promoted some water column mixing and the entrainment of nutrients from bottom sediments or from adjacent water masses.